Enhancement of the tidal disruption event rate in galaxies with a nuclear star cluster: from dwarfs to ellipticals. Issue 2 (7th July 2020) - Pfister, Hugo; Volonteri, Marta; Dai, Jane Lixin; Colpi, Monica
ABSTRACT: We compute the tidal disruption event (TDE) rate around local massive black holes (MBHs) with masses as low as $2.5× 10^4\, M_{\odot }$, thus probing the dwarf regime for the first time. We select a sample of 37 galaxies for which we have the surface stellar density profile, a dynamical estimate of the mass of the MBH, and 6 of which, including our Milky Way, have a resolved nuclear star cluster (NSC). For the Milky Way, we find a total TDE rate of ${\sim}10^{-4}\, yr^{-1}$ when taking the NSC in account, and ${\sim}10^{-7} \, yr^{-1}$ otherwise. TDEs are mainly sourced from the NSC for light (${\lt}3× 10^{10}\, M_{\odot }$ ) galaxies, with a rate of few $10^{-5}\, yr^{-1}$, and an enhancement of up to two orders of magnitude compared to non-nucleated galaxies. We create a mock population of galaxies using different sets of scaling relations to explore trends with galaxy mass, taking into account the nucleated fraction of galaxies. Overall, we find a rate of few $10^{-5}\, yr^{-1}$ which drops when galaxies are more massive than $10^{11}\, M_{\odot }$ and contain MBHs swallowing stars whole and resulting in no observable TDE.